Methodology: U.S. Army Alaska 2006 Range Developments Section 106 Archaeological Inventory and Evaluation Fort Richardson and Fort Wainwright - Robertson, Aaron C.; Proue, Molly (Center for the Environmental Management of Military Lands (CEMML), 2006)
U.S. Army Alaska planned to survey several past inventoried archaeological sites during the 2006 summer field season. The focus of this work would involve: 1) the survey of firing fans associated with training ranges on Fort Wainwright's Yukon and Donelly Training Areas, 2). Evaluations to determine eligibility for inclusion in the National Register of Historic Places of archaeological sites that may be impacted by future development on the Donnelly Training Area, and 3). Numerous smaller Section 106 surveys at Fort Wainwright, including the Donnelly Training Area, and Fort Richardson. This document presents the archaeological potential of U.S. Army Alaska lands, the areas to be surveyed and the methodology that was used in those surveys.